Screening of lactic acid bacteria in Cupei of vinegar and the application in the fermentation of liquid-state apple cider vinegar - WANG Li, XIONG Feng, WANG Bei, HAN Lihua, TIAN Xiaoyu, ZHANG Xiaorui (Zhongguo niangzao, 2025)
The lactic acid bacteria in the Cupei of Zhenjiang vinegar were isolated and screened by high-throughput sequencing technology and plate method. The isolated strains were identified through morphological observation and 16S rDNA sequencing, and the suitable growth temperature, acetic acid and ethanol tolerance of the strains were studied. Then they were applied to the fermentation of liquid apple cider vinegar. The difference changes in physiochemical indicators and volatile flavor substances after the bacteria participated in the fermentation of apple cider vinegar were analyzed. The results showed that the main screened lactic acid bacterium were Lactobacillus acetotolerans L-1. The suitable growth temperature was 30 ℃. It could still grow well when the mass concentration of acetic acid was <3 g/100 ml and the volume fraction of ethanol was <9%, and had strong acid and ethanol tolerance. L. acetotolerans L-1 could increase the mass concentration of non-volatile acid in apple cider vinegar (0.39 g/100 ml). Meanwhile, gas chromatography-mass spectrometry analysis indicated that the content of volatile flavor substances in apple cider vinegar prepared by the synergistic fermentation of L. acetotolerans L-1 was higher, reaching 22.20 mg/L. Among them, the types and mass concentrations of ester substances increased significantly, especially substances with floral and fruity aroma such as isopentyl acetate, phenethyl acetate, ethyl octoate, and ethyl decanoate.